Richter Syndrome - Condoluci, Adalgisa (Curr Oncol Rep, 2021)
PURPOSE OF REVIEW: Richter syndrome (RS) is an uncommon but aggressive evolution of chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL). RS is an unmet clinical need in the field of CLL. Recent advances in understanding the biology of this condition provide the rationale for testing new therapeutic concepts in order to improve the outcome of patients developing RS, which is so far poor. In this review, we summarize disease characteristics and available therapeutic options for RS. RECENT FINDINGS: Current regimens with novel agents in monotherapy have shown little impact on survival. Nevertheless, the better reported outcome for RS has been achieved with the combination of chemo-immunotherapy with a novel agent, confirming the synergistic effect of the approaches. Still, the frailty of this population may impose a less toxic management leaving most patients with no reasonable therapeutic option. SUMMARY: Treatment options for RS need to be further expanded. Preclinical models in current development may allow to explore actionable pathways and identify new drug targeted combinations.